The fracture behaviour of notched PMMA specimens under simple loading conditions – Tension and torsion experimental tests. (June 2023) - Bura, Elżbieta; Seweryn, Andrzej
Highlights: Experimental results of tension and torsion experimental tests on notched specimens. Various fracture initiation points and moments for different root radii and loading conditions. Fracture evolution processes for each notch type – high-speed photography. Abstract: This paper presents the results of experimental testing of flat PMMA specimens during uniaxial loading conditions. Two separate tests were conducted: tensile and torsion. The specimens were weakened with V-type edge notches with different root radii: 0.5; 2 and 10 mm. The specimens were made in two thickness variants: 5 and 15 mm. Monotonic tensile and torsion tests were carried out while keeping the averaged strain rate constant, due to the strong influence of this parameter on the PMMA behaviour. The procedure for non-contact measurement of the torsion angle using the ARAMIS 3D 4 M vision system is described. A set of PHANTOM cameras was used in the study, thanks to which all fracture processes were recorded. The processing of the obtained recordings made it possible to precisely indicate the moment (critical value of tensile force, torsional moment) and the location of crack initiation, as well as determine the nature of their evolution. Microscopic observations showed the structure of the failure surface and clearly indicated the different initiation sites observed for the two simple loading states. Different crack initiation angles were indicated, depending on the type of test conducted, as well as the notch root radius. The material in the article provides a starting point for numerical modelling of the fracture processes of notched elements and verifying the fracture criteria.